The choice of tactics for surgical treatment of abdominal aortic aneurysm in octogenarians - V. S. Arakelyan; N. A. Chernykh; V. G. Papitashvili; R. G. Bukatsello («REMEDIUM GROUP» Ltd., 2023)
Currently, the treatment of abdominal aortic aneurysm does not pose significant difficulties, with modern cardiovascular surgery offering the possibility of both open and endovascular repair (EVAR) techniques. However, the personalized selection of the most optimal surgical intervention for each patient remains a relevant question. In some cases, one of the important factors influencing the choice of surgical method is the patient's age and accompanying diseases. Abdominal aortic aneurysm is an age-related condition with a high risk of fatal outcomes. In our practice, we encountered a rare case of abdominal aortic aneurysm in an octogenarian woman with severe somatic status, poorly controlled arterial hypertension, and complex anatomical enlargement of the aneurysm. The question arose regarding the choice of optimal tactics and surgical treatment method. According to the MSCT, the diameter of the expansion was 67 mm, posing a 20% risk of rupture in the first year. In this clinical case, EVAR technique was unsuitable due to the anatomical features of the aneurysm, as the length of the neck in the infrarenal segment of the aorta was 2.5-3 cm, and the angle of inclination to the right exceeded 85°. Additionally, considering gender-specific factors, particularly female gender, indications for EVAR need to be carefully determined, as women have a higher likelihood of complications following the operation, as shown in several studies. After a detailed analysis of the re-evaluation results and assessment of surgical risk factors, we determined an individual surgical strategy and minimized risks, ultimately achieving a good outcome.